Intervention of Army Aviation in Natural Disasters and Its Relation to National Development: Case of the El Niño Phenomenon in the Piura Region - Uribe Muñante, Fernando Javier (2020)
The research work entitled “Army aviation intervention in natural disasters and its relationship with national development: case of the phenomenon of children in the Piura Region in 2017”, aimed to determine the relationship between the intervention of the Aviation of the Army in Natural Disasters and National Development in the case of the El Niño phenomenon in the Piura Region, 2017. A quantitative approach investigation was conducted, the scope was correlational and the design was non-experimental and correlational in cross-section. The target population was made up of 89,799 people, made up of (01) General Officer, Senior Officers, Junior Officers, Technicians and Sub-Officers, civilian personnel from Army Aviation and the staff of victims of the El Niño phenomenon in the Piura Region. The sampling was simple random to estimate proportions, obtaining an optimal sample of 383 people; In addition, the observation techniques were applied and the instrument used was the Likert-style survey, made up of 18 items, which was directed at the optimal sample. It was concluded, with a significance level of 95%, that there is a high positive correlation between the intervention of Army Aviation in natural disasters and national development; In addition, a Spearman’s Rho coefficient was shown = 0.891 confirming that the intervention of Army Aviation with its equipment, aeronautical units and highly specialized personnel support national development, which confirmed that there is a high correlation between the intervention of the Army aviation in natural disasters and national development